PRODUCTIVITY OF TOMATO PLANTS PULVERIZED WITH CALCIUM AND BORON ON THE NUMBER OF RODS - A. R. Zeist (Scientific Electronic Archives, 2016)
Context in which mineral nutrients Ca and B and the form that plants are conducted has great influence on productive aspects of the tomato crop. The objective of this research was to evaluate the effect of tomato foliar sprays of Ca and B, and the number of stems. To run the experiment genotype tomato hybrid Absolute®, belonging to the group salad, the plot was sprayed with all combinations (C) possible for (calcium (Ca) + boron (B)), and the subplot about the number of rods: (H1 - (one rod) and H2 - (two rods)). Throughout the cycle were evaluated: number of marketable fruits (CF) and non-commercial (FNC) and marketable fruit yield (PFC) and non-commercial (PFNC). According to the results, it was found that there was only interaction to the number of non-marketable fruit variable. By means of spraying, it was found that the isolated foliar application of B, can increase the number of commercial fruit, and the combined foliar application of (Ca + B), allows to decrease the production of non-commercial fruits. And as to the number of rods, that driving with two tomato stem is more appropriate.